Pengaruh Leverage, Ukuran Perusahaan, dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Subsektor Industri Makanan dan Minuman Dengan Profitabilitas Sebagai Moderasi Periode 2021-2023 - Martin Irawan; Edrick Forbes; Adrian Salim; Angelly Simmon (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to analyze and test the effect of leverage, company size, and liquidity on company value and the ability of profitability to moderate the effect of leverage, company size, and liquidity on company value in manufacturing companies in the food and beverage industry sub-sector that have been listed on the Indonesia Stock Exchange for the period 2021-2023. The population of this study consisted of 26 food and beverage sub-sector manufacturing companies. The sampling method used in this study used purposive sampling technique and resulted in sample data of 72 companies used in this study. The data analysis method used in this study is multiple regression analysis which was previously tested with classical assumptions, then moderation testing will be carried out with the MRA test. The results of this study explain that leverage, company size and liquidity have no effect on company value and profitability is able to moderate the relationship between company size and company value, but cannot moderate the relationship between leverage and liquidity on company value.